The Influence of Leadership Style and Company Culture on Organizational Commitment in Improving Employee Performance at PT. Toyofuji Logistics INDONESIA (MEMBER OF ASTRA) - Hardian Abdi; Iman Sofian Suriawinata; Indra Sakti (Indonesian Journal of Business, Accounting and Management (IJBAM), 2020)
The study aimed to identify the style of leadership and corporate culture of the commitment to improve employee performance in PT. Toyofuji Logistics Indonesia (member of astra). The methodology this is quantitative methods using data primary .The total sample of the research is about 88 employees. Data processing in this study used a smartpls analysis, and the analysis in a partial least squares. The result showed that, (1) corporate culture have a positive influence on the performance and significant, employees (2) corporate culture have a positive influence on, organization and significant commitment (3) leadership style has a negative and insignificant to employee performance (4) leadership style and have a positive influence significantly to the organization and the organization have a positive influence on the performance and significant employee